Hepatic Hydatid Cyst in a Turkana Woman - case report - Zeyhle, E.; Magambo, J.K.; Wachira, J.; Gikandi, A.; Njoroge, E.M. (African Journal of Health Sciences, 1999)
An unusual case of hepatic hyd:1tid cyst in a 27-year old female is reported. The patient had nbdominal distension of 111-year duration, pain, 1>allor of mucous membranes, and was grossly w:1sted. Ultrasono~rnphy revealed a large hydatid cyst that covered most of the abdomen. A successful suq.:ical intcnention was performed and 24 litres of hydatid fluid drained.
Case study